2014
DOI: 10.1111/tan.12340
|View full text |Cite
|
Sign up to set email alerts
|

SSX2‐4 expression in early‐stage non‐small cell lung cancer

Abstract: The expression of cancer/testis antigens SSX2, SSX3, and SSX4 in non-small cell lung cancers (NSCLC) was examined, since they are considered promising targets for cancer immunotherapy due to their immunogenicity and testis-restricted normal tissue expression. We characterized three SSX antibodies and performed immunohistochemical staining of 25 different normal tissues and 143 NSCLCs. The antibodies differed in binding to two distinctive splice variants of SSX2 that exhibited different subcellular staining pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Previous studies show that HCT116 do not express NY-ESO-1 and SSX-2 proteins (24)(25)(26)(27). In our current study, we confirmed that cancer-specific CTLs did induce IFNg and TNFa in cocultures with HCT116 cells in the absence of external peptide loading (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies show that HCT116 do not express NY-ESO-1 and SSX-2 proteins (24)(25)(26)(27). In our current study, we confirmed that cancer-specific CTLs did induce IFNg and TNFa in cocultures with HCT116 cells in the absence of external peptide loading (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Prior to culturing, target cells were externally loaded with corresponding peptides (SSX-2 or NY-ESO-1, 10 mg/mL) at 37 C for 1 hour to enable the loading and presentation of the peptides on the MHC complex on the target cell surface. HCT116 is a commercially available cancer cell line that is known to be HLA-A2 þ , E-Cadherin þ (the ligand for CD103) and does not express SSX-2 and NY-ESO-1 proteins (24)(25)(26)(27). Another condition was also included by using THP-1 as target cells, which is E-Cadherin -HLA-A2 þ SSX-2 -NY-ESO-1 -.…”
Section: Target Cell Lines Used For In Vitro Functional Assaysmentioning
confidence: 99%
“…The Synovial Sarcoma, X-breakpoint (SSX) family comprises six highly similar members with additional splicing variants (i.e., SSX1, SSX2, SSX3, SSX4, SSX5 and SSX7) and several pseudogenes [75]. The proteins are strictly expressed in the spermatogonia of testis in healthy individuals, but ectopic expression is found in many different types of human cancer [76,77]. The proteins are most frequently detected in melanoma, where approximately 40% of tumors are positive for SSX2, SSX3 or SSX4 [78].…”
Section: The Ssx Family Of Chromatin-modulating Proteinsmentioning
confidence: 99%
“…SSX proteins are germ cell-specific proteins that are expressed at the spermatogonial stage of spermatogenesis 11 . They are also ectopically expressed in many types of tumors, such as 40% of melanomas and up to 65% of breast cancers 12,13 . The SSX family comprise nine highly identical members, which are most likely redundant in their cellular functions 14 .…”
Section: Introductionmentioning
confidence: 99%